Family Based Aged’s Social Service - Etty Padmiati; Kissumi Diyanayati (Jurnal Penelitian Kesejahteraan Sosial, 2015)
This research was meant to know the family, as aged’s problem handling place, to do in fulfilling aged needs, and its enfluencial factors. The research took place in Krembangan Village, Panjatan district, Kulonprogo Regency, Yogyakarta Special Teritorry. Informants were ditermined through purposive sampling, as many nine aged persons including theirfamiles that looked after them. Data were gathered through interview, observation, documentary analysis. Data were analysed through qualitative-descriptive technique. The result showed that families gave social service to aged member of the family, phisically, psychologically, and socailly. The enfluencial factors in giving the service to their aged member of the family were the family income, the number of the family they hold, their interaction and communication process, and the condition and aged ability. Based on the result, to enhance the role of the family to give social service to their aged member, it need social guidance and information to the family related to the aged problem and need, so that the family know the need of phisical, psychological, and social needs of aged.